Efeito do exercício físico agudo realizado até a interrupção voluntária do esforço na temperatura ambiente de 12 oC e 25 oC sobre a temperatura hipotalâmica - Cletiana Goncalves da Fonseca (2012)
This study investigated the effect of physical exercise on the temperature in the ventromedial nucleus hypothalamus (VMH) during treadmill running with constant-speed exercise until voluntary interruption of the effort (VIE), at ambient temperature of 12 oC and determine maximum speed of running during incremental-speed exercise at ambient temperatures of 12 oC and 25 oC until the voluntary interruption of the effort. For that purpose, adults Wistar rats were utilized. They weighted between 250 365 g. The rats were subjected to the implant of a guide cannula in the right ventromedial hypothalamic nucleus and of an abdominal temperature sensor. After recovery from surgery, the rats were familiarized with running (18 mmin-1 and 5% inclination) during five consecutive days. Then the rats in protocol 1 were subjected to the following experimental trials: constant-speed exercise of 20 mmin-1 and 5% inclination, at ambient temperatures of 12 oC and 25 oC, 60 minutes rest in the treadmill at ambient temperature 12 oC and 60 minutes rest in the cage at ambient temperature of 25 oC. The rats in protocol 2 were subjected to running with incremental-speed exercise until VIE, at ambient temperature of 12 oC e 25 oC. The temperature in the VMH increased during constant-speed exercise until interruption voluntary of the effort, at ambient temperature of 25 oC (37.68 ± 0.06 oC min zero vs. 39.16 ± 0.09 oC VIE; n = 7; p < 0.001). However, the temperature in the VMH remained unchanged from start to finish of exercise performed until voluntary interruption of the effort, at ambient temperature of 12 oC (37.39 ± 0.28 oC min zero vs. 37.71 ± 0.20C VIE; n = 6; p = 0.63). These data indicate that the heat dissipated during physical exercise at a thermoneutral environment was not sufficient to maintain the thermal balance, inducing to an increase of temperature in the VMH. Nevertheless, the heat dissipated during exercise in the cold environment counterbalanced the heat produced in the brain and in the muscles, resulting unchanged of the temperature in the VMH. Moreover, the physical performance during the constant-speed exercise realized at ambient temperature of 12 oC was 112% higher as compared to exercise in a thermoneutral environment (67.1 ± 13.7 min 12 oC vs. 31.5 ± 5.6 min 25 oC; n = 7; p = 0.04). Also, during incremental-speed exercise, the physical performance was 16% higher as compared to exercise in thermoneural environment (31.2 ± 0.7 mmin-1 12 oC vs. 26.4 ± 1.7 mmin-1 25 oC; n = 9 7; p = 0.01). These results indicate that hypothalamic temperature of the rats remained unchanged from start to finish of the physical exercise resulting in higher performance